Multicenter study evaluating the impact of COVID-19 outbreak on dermatology outpatients in Turkey - Kartal, Selda Pelin; Celik, Gokcen; Sendur, Neslihan; Aytekin, Sema; Serdaroglu, Server; Dogan, Bilal; Alpsoy, Erkan (Wiley, 2020)
COVID-19 pandemic has a significant impact on public health, whether directly or indirectly. The first case was seen in Turkey on March 11, and the World Health Organization (WHO) declared a pandemic on March 12, 2020. The study aimed to document the effect of pandemic on dermatology outpatient clinics in Turkey. Fifteen tertiary hospitals from 13 provinces were included in the study, which was conducted between January 12 and May 12, 2020. The International Codes of Diseases (ICD-10) categories and patients' characteristics were evaluated before and after the pandemic. A total of 164 878 patients, 133 131 before and 31 747 after the pandemic, were evaluated. The daily hospital applications were found reduced by 77%. The three of the most frequent diagnoses; dermatitis, acne, and psoriasis remained unchanged after the pandemic. While the frequency of herpes zoster, scabies, urticaria, pityriasis rosea and sexually transmitted diseases increased significantly; allergic and irritant contact dermatitis decreased after the pandemic. The applications regarding cutaneous neoplasms were considerably reduced during the pandemic, and this effect was more pronounced in cities with higher COVID incidence. The pandemic caused a noteworthy reduction in the number of patients accessing dermatological care. The pandemic caused significant changes in the frequency of a wide range of dermatological diseases. The application of cutaneous neoplasms is considerably reduced after the pandemic, and this effect was more pronounced in cities where pandemics are frequent. Therefore, the pandemic has resulted on numerous impacts on many critical issues in dermatology and dermatological care.
Keywords: COVID-19; dermatology outpatients; pandemic